2012
DOI: 10.1258/acb.2011.011258
|View full text |Cite
|
Sign up to set email alerts
|

Elevated human epididymis protein 4 concentrations in chronic kidney disease

Abstract: HE4 concentrations may be elevated in CKD patients with no ovarian and lung cancer. Thus, HE4 results should be interpreted cautiously in women with renal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 18 publications
5
89
0
1
Order By: Relevance
“…The association of HE4 levels with kidney function has also been replicated in cohorts comprised of acute and chronic HF patients [75,76]. It has been suggested that the elevated levels of HE4 in CKD patients may complicate its use in monitoring patients with epithelial ovarian cancer [82], and the same is probably true in the HF setting. These multi-disease effects on HE4 plasma levels will mean that HE4 will not be useful for HF diagnosis, but, as part of a multi-biomarker model, it may have potential in the stratification of HF patients.…”
Section: Fibrosis Marker He4mentioning
confidence: 91%
“…The association of HE4 levels with kidney function has also been replicated in cohorts comprised of acute and chronic HF patients [75,76]. It has been suggested that the elevated levels of HE4 in CKD patients may complicate its use in monitoring patients with epithelial ovarian cancer [82], and the same is probably true in the HF setting. These multi-disease effects on HE4 plasma levels will mean that HE4 will not be useful for HF diagnosis, but, as part of a multi-biomarker model, it may have potential in the stratification of HF patients.…”
Section: Fibrosis Marker He4mentioning
confidence: 91%
“…Compared with 68 healthy females, a significant positive correlation between increasing severity of renal failure and elevated serum HE4 levels was found in both the pre-and postmenopausal group (P ¼ 0.003-0.0001 and P ¼ 0.001-0.0001, respectively; ref. 41). Liver disease has been proved to induce only small, yet, significant increases in serum HE4 levels (P ¼ 0.001) in one study (13).…”
Section: Serum Levels Of He4 In Healthy Individualsmentioning
confidence: 93%
“…Finally, patients with renal failure have been demonstrated to have significantly increased serum HE4 concentration correlating to elevated serum creatinine levels (13,21,35,41,42). One study measured serum HE4 in a group of 113 female patients at different stages of chronic kidney disease with no history of ovarian cancer or lung cancer.…”
Section: Serum Levels Of He4 In Healthy Individualsmentioning
confidence: 99%
“…Renal failure was identified to be an important cause of increased serum HE4 in nonmalignant patients [86,95]. Nagy and colleagues compared serum HE4 and CA125 levels in patients of chronic kidney disease (CKD) [96]. They found that an elevated HE4 level was present at the early stage (stages 1 and 2) of CKD, but CA125 values were only significantly increased in advanced CKD stages (stages 4 and 5), compared to healthy individuals, suggesting that HE4 was more likely increased in CKD than CA125.…”
Section: He4 Expression In Urinary System and Renal Cancersmentioning
confidence: 99%